Effects of anxiety on running with and without an aiming task - Nibbeling, N.; Daanen, H. A. M.; Gerritsma, R. M.; Hofland, R. M.; Oudejans, R. R. D. (Journal of Sports Sciences, 2011)
State anxiety is known to affect far aiming tasks, but less is known about the effects of state anxiety on running and aiming while running. Therefore, in the current study participants ran on a treadmill at their preferred speed in a low- and high-anxiety condition. In both conditions, running was combined with dart throwing in the last minutes. Results showed that attention shifted away from task execution with elevated levels of anxiety. Furthermore, gait patterns were more conservative and oxygen uptake was higher with anxiety. In addition, performance and efficiency on the dart throwing task also decreased with anxiety. These findings are in line with attentional control theory and provide an indication that state anxiety not only affects aiming tasks but also tasks that rely heavily on the aerobic system. Moreover, findings indicate that when combined, running, aiming, and anxiety all compete for attention leading to suboptimal attentional control and possibly a decrease in performance.